Application of Liquid Smoke from Rubber Wood Clone PB-340 as Latex Coagulant and Preservation of Natural Rubber Coagulum - Maria Magdalena Sinaga; Djagal Wiseso Marseno; Manikharda Manikharda (agriTECH, 2023)
The utilization of rubber wood waste in the form of liquid smoke has the potential to overcome environmental problems caused by the industry. Therefore, this study aimed to determine the potential of liquid smoke from rubberwood clone PB 340 to be used as a coagulant and preservative. Rubber wood waste was processed into liquid smoke using the pyrolysis method with a temperature of 400°C. Determination of the composition of liquid smoke was carried out using gas chromatography-mass spectrometry (GC-MS) analysis. The results showed that the rubber wood clone PB 340 contained 57.78% cellulose, 12.16% hemicellulose, and 19.01% lignin. Furthermore, volatile analysis with GC-MS showed that liquid smoke from rubber wood clone PB 340 contained 58 organic compounds. Some compounds in liquid smoke were phenols, furans, furfurals, acetic acid, and cyclopentene. The product was then tested for its performance as a latex coagulant at several concentrations of 5%, 10%, 15%, 20%, and 25% v/v, as well as storage time of 1, 7, and 14 days. The treated latex samples that had turned into coagulums were examined for their sheet quality parameters, including initial plasticity (P0), plasticity retention index (PRI), total volatile compounds, impurity, and ash content. The outcomes from all comparisons of pure liquid smoke concentrations and storage time of up to 14 days of the coagulum samples showed that in the initial plasticity value (P0), the plasticity retention index (PRI), volatile matter, ash content, and dirt content had met the applied Standard Indonesian Rubber (SIR).